Vocal nodules in a colombian teachers group with dysphonia - Andrés Felipe Alvarado Díaz; Carlos Eduardo Pinzón; José Rafael Tovar Cuevas; Adriana Fajardo Hoyos (Escuela Nacional de Medicina del Trabajo, 2013)
Objectives: This study determined the prevalence of vocal nodules associated with dysphonia in teachers aged from 35 to 65 years, taking into consideration both individual and occupational variables. Methodology: Descriptive study that included the information contained in 262 medical records of teachers diagnosed with dysphonia in occupational health consultations at the institutions that provide health services in Bogotá, Colombia from March 2009 to March 2012. The presence of laryngeal nodules was based on the findings of a nasofibrolaryngoscopy procedure. Results: Nodules were found in 67 teachers, which corresponded to a rate of 25.5%, being apparently (highest observed rates) associated primarily with the following variables: females, ages from 45 to 54 years, bilateral nodules, and teaching position (preschool and physical education). Of the teachers with nodules, 76.1% had fewer than five doctor's appointments, and 75% had more than 90 days of sick leave. Conclusion: A high percentage of teachers have vocal nodules associated with dysphonia. This may be apparently related to different variables such as sex, type of nodule, area and teaching position. Was observed only a statistically significant association among presence of nodules and age (p=0.018). In addition this disorder generates a large number of incapacities and employee absenteeism.